A Danian subtropical lacustrine palynobiota from South America (Bororó Formation, San Jorge Basin, Patagonia - Argentina) - L. SCAFATI; D.L. MELENDI; W. VOLKHEIMER (Geologica Acta, 2009)
New results on a lacustrine Danian palynological association in extra-andean northern Patagonia (lower member of the Cerro Bororó Formation, San Jorge Basin, Chubut province, Argentina) are presented. This is a contribution to the largely unexplored field of Paleogene freshwater environments. The palynobiota includes representatives of the kingdoms Protoctista and Plantae. Twelve of the aquatic species are Protoctista. From the nine Chlorophyta form-species, four correspond to Botryococcaceae, one to Coelastraceae and four to Zygnemataceae (Gelasinicysta, Schizosporis, Ovoidites, and Pseudoschizaea). The remaining forms are dinoflagellate cysts (Peridinium and dinocyst indet.) and prasinophyceans (Leiosphaeridia). Plants are represented by spores and pollen of Bryophytes (Sphagnaceae and Ricciaceae), Pteridophytes (Salviniaceae), and Angiosperms (Arecaceae, Araceae and Sparganiaceae/Typhaceae, the latter representing macrophytes living in or near the swampy areas). Other palynomorph groups closely related with biotopes of permanent moisture are dominated by spores of the families Selaginellaceae, Lycopodiaceae, Cyatheaceae, Schizaeaceae, Polypodiaceae and Psilotaceae. The palynological assemblage reflects a freshwater lacustrine environment that developed in a marine coastal zone nearby brackish coastal swamps. Based on the composition of the palynoflora including palm pollen and other thermophilous taxa, humid, warm climatic conditions are inferred for the area of deposition.